PROFESSIONAL EXAMINATIONS. - Chamberlain, Henry T. (The Accounting Review, 1939)
Abstract This article presents the problems and answers which were presented as the first half of May 1939, Certified Professional Accountant examination in the U.S. In problem 1, the candidates were required prepare a statement showing the amounts payable to different beneficiaries. In problem 2, the case history of the Universal Patent Corporation was given. The Universal Patent Corporation acquired 700 shares of the capital stock of the General Development Company. The shareholders of the General Development Company ordered the liquidation of the company as at the close of December 31, 1938. The shareholders were to receive a pro-rata assignment of their interest in the patent on January 2, 1939. The candidates were asked to prepare the entries which the Universal Patent Corporation should make to record the amortized cost of its interest in the patent on the date of assignment. Problem No. 3 stated that a governmental authority was constituted about July 1, 1937, to carry out certain recreational activities for which the authority was to buy or construct the equipment. The candidates had to prepare a columnar work sheet recording the transactions of the authority so as to show the asset and liability and budgetary accounts for the year ended June 30,1938.